Getting to the Heart of System Reform – A micro strategy for large scale educational change - David Hopkins; John Baumber (Educational Futures)
There is a paradox at the heart of contemporary system change in education. On the one hand there is the unequivocal conclusion from the accumulation of PISA evidence for example, that both excellence and equity are possible at a system level; yet on the other hand there are concerns from most educational jurisdictions over the stubbornness of low standards. Why is it that despite the phenomenal increase in our recent knowledge about what works in schooling, that standards still lag behind expectations and school level performance is far too variable. The paper addresses this paradox and concludes that unless we focus unrelentingly on the quality of teaching in both our small and large-scale reform efforts, then current practice will never meet society’s expectations. A ‘micro-strategy’ for sustained systemic educational change, generally known as ‘Instructional Rounds’, is described. This strategy for pedagogic improvement has the potential for generating an increasingly specific language for teaching and learning that significantly aids consistency and precision in the quest for both excellence and equity. The argument concludes by proposing a school improvement strategy for moving Instructional Rounds, the generation of Theories of Action and Peer Coaching to scale. This has particular relevance for school networks and Multi Academy Trust and has the potential of having has the potential of having large-scale system reform impact.